2004
DOI: 10.1111/j.1365-2044.2004.03713.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised, single‐blind pilot study to determine the effect of anaesthetic technique on troponin T release after off‐pump coronary artery surgery

Abstract: SummaryIschaemic damage to the myocardium inevitably occurs during coronary artery surgery. However, the extent of the damage may be influenced by the anaesthetic technique used. The most sensitive and reliable marker of myocardial damage is currently thought to be troponin T. We conducted a prospective, randomised, single-blind pilot study to determine the baseline values of troponin T release after off-pump coronary artery bypass surgery in 30 patients randomly allocated to receive either propofol, isofluran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…We did not observe a significant effect of desflurane on blood concentrations of markers of myocardial ischaemia: troponin I and CK-MB. Earlier studies demonstrated conflicting results: a decreased concentration after volatile anaesthesia [12,14], or no effect [10,[15][16][17][18]. In two studies published recently, late postconditioning with sevoflurane used for sedation after coronary surgery also did not provide reduction of troponin release [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe a significant effect of desflurane on blood concentrations of markers of myocardial ischaemia: troponin I and CK-MB. Earlier studies demonstrated conflicting results: a decreased concentration after volatile anaesthesia [12,14], or no effect [10,[15][16][17][18]. In two studies published recently, late postconditioning with sevoflurane used for sedation after coronary surgery also did not provide reduction of troponin release [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…[4,14,15,47,48] A recent randomized study demonstrated that isoflurane, administered in low minimum alveolar concentration through the precardiopulmonary bypass reduces postoperative catecholamine requirements of cardiac surgery patients. [49] There are at least three different mechanisms in the cellular or sub cellular levels involved in this volatile anesthetic protection, and all of them were out of the scope of our present study:…”
Section: Protective Effects Of Propofolmentioning
confidence: 99%
“…A review of the medical literature reveals that the effects of propofol on myocardial stunning after transient ischemia have not been properly investigated, and that in vivo it was far from being advantageous, [8,9,11,12,14,[16][17][18]32] even though there is some evidence (mostly in in vitro studies) for its potential to protect the ischemic myocardium. [13,15,[33][34][35][36][37][38] The purpose of this study was to compare the effects of propofol vs isoflurane in a porcine model of acute coronary occlusion, imitating postischemic reversible contractile dysfunction conditions that may appear in off-pump cardiac surgery. We investigated the hypothesis that volatile anesthetic isoflurane improves global myocardial function, following transient coronary occlusion and reperfusion when compared to the short-acting intravenous anesthetic, propofol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One emerging problem is that some researchers (or their critics) are placing far too much emphasis upon power analysis [28]. One example demonstrates the type of misplaced faith in power analysis: ‘…at least 400 patients would be required to prove there is no statistically significant difference between the groups…’[29] (our emphasis). Such statements reveal a poor understanding of the scientific method and of the concept of scientific proof.…”
Section: Ranges Of Sample Sizes Commonly Used In Different Types Of Smentioning
confidence: 99%